The Result of Transmuscular versus Transosseous Repair of the Posterior Capsule on Early Dislocations in Primary Hip Arthroplasty. Issue 6 (November 2015) - Spaans, Elsa A.; Spaans, Anne J.; van den Hout, Joost A.A.M.; Bolder, Stefan B.T.
Purpose: Dislocation is a concerning complication of the posterolateral approach for total hip arthroplasty (THA). Use of a larger size femoral head and a correct repair of the posterior structures can reduce the risk on dislocation of the hip prosthesis. In this study we investigated if there was a difference in dislocation rate between transmuscular and transosseous repair of the posterior soft tissues with use of 36 mm heads. Methods: A power analysis showed that with a standardised effect size of 0.3 and p-value of 0.05, each group should include at least 174 patients. A total of 465 consecutive primary THAs with a posterolateral approach were performed in patients with primary osteoarthritis by 3 orthopaedic surgeons. There were 246 patients operated using transmuscular repair, the other 219 by using transosseous repair. All patients were given the same prostheses. Results: Dislocation rate was 1.7% in all patients with at least 1 year follow-up. No significant difference was found in dislocation between both reconstruction techniques. Clinical outcome scores were comparable between the groups. Conclusions: Transosseous and transmuscular repair were equally effective techniques in closing the posterior soft tissues after THA through the posterolateral approach, without difference in dislocation rate or complication rate.